2021
DOI: 10.3390/coatings11121493
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Experimental Study on Influencing Factors of Drainage Pipe Crystallization in Highway Tunnel in Karst Area

Abstract: The crystalline blockage of tunnel drainage pipes in a karst area seriously affects the normal operation of drainage system and buries hidden dangers for the normal operation of the tunnel. In order to obtain the influencing factors and laws of tunnel drainage pipe crystallization in a karst area, based on the field investigation of crystallization pipe plugging, the effects of groundwater velocity, drainage pipe diameter, drainage pipe material, and structure on the crystallization law of tunnel drainage pipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The partial pressure of CO 2 has a great relationship with carbonate crystallization sedimentation, and CO 3 2 − is mainly derived from CO 2 dissolved in groundwater [ 31 ]. Liquid velocity, liquid level height, drainage pipe diameter, and the internal wall friction coefficient will also have an important impact on the precipitation crystallization rate of drainage pipes [ 37 , 38 , 39 ]. The precipitation of calcium carbonate depends not only on the hydraulic conductivity and CaCO 3 content of surrounding rock, but also on the properties of lining materials and the geometry of the tunnel [ 40 ].…”
Section: Construction and Analysis Of A Fault Tree Model For Blocked ...mentioning
confidence: 99%
“…The partial pressure of CO 2 has a great relationship with carbonate crystallization sedimentation, and CO 3 2 − is mainly derived from CO 2 dissolved in groundwater [ 31 ]. Liquid velocity, liquid level height, drainage pipe diameter, and the internal wall friction coefficient will also have an important impact on the precipitation crystallization rate of drainage pipes [ 37 , 38 , 39 ]. The precipitation of calcium carbonate depends not only on the hydraulic conductivity and CaCO 3 content of surrounding rock, but also on the properties of lining materials and the geometry of the tunnel [ 40 ].…”
Section: Construction and Analysis Of A Fault Tree Model For Blocked ...mentioning
confidence: 99%
“…The results show that the crystallisation rate of karst water is mainly influenced by the roughness of the pipe wall and, to a lesser extent, the slope of the pipe. Li et al 14 studied the effects of groundwater flow rate, drainage pipe diameter, drainage pipe material and structure on the crystallisation pattern of tunnel drainage pipes in karst areas through indoor model tests and achieved significant conclusions. Eichinger et al 15 found that Ca (OH) 2 is readily soluble in water and analysed the factors responsible for pipe blockages, focusing on the effect of CaCO 3 on pipe blockages, showing that a small number of ettringite precipitates at high pH and in saturated solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, China has made many technological breakthroughs in tunnel construction, making it a tunnel powerhouse [1]. The construction and operation of tunnels lead to crystal blockage of tunnel drainage pipes (such as Chongqing [2], Yunnan [3], Sichuan [4], and Guizhou (Figure 1). After crystal blockage takes place in drainage pipes, the groundwater around the lining cannot be discharged from the tunnel in time, resulting in a number of defects such as increased water pressure in the lining, lining cracking and leakage, water overflow in the tunnel [5,6], severely threatening tunnel lining and operation safety.…”
Section: Introductionmentioning
confidence: 99%